2017
DOI: 10.3389/fmicb.2017.02394
|View full text |Cite
|
Sign up to set email alerts
|

Secretome Characterization and Correlation Analysis Reveal Putative Pathogenicity Mechanisms and Identify Candidate Avirulence Genes in the Wheat Stripe Rust Fungus Puccinia striiformis f. sp. tritici

Abstract: Stripe (yellow) rust, caused by Puccinia striiformis f. sp. tritici (Pst), is one of the most destructive diseases of wheat worldwide. Planting resistant cultivars is an effective way to control this disease, but race-specific resistance can be overcome quickly due to the rapid evolving Pst population. Studying the pathogenicity mechanisms is critical for understanding how Pst virulence changes and how to develop wheat cultivars with durable resistance to stripe rust. We re-sequenced 7 Pst isolates and include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 94 publications
2
46
0
Order By: Relevance
“…This can be explained by the property of Pst and EMS mutagenesis. i) The two nuclei in Pst urediniospores were found to be highly heterozygous in many isolates [37,39,58,59]. ii) Previous studies observed Pst isolates with a low virulence spectrum tended to be highly heterozygous [39,60].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This can be explained by the property of Pst and EMS mutagenesis. i) The two nuclei in Pst urediniospores were found to be highly heterozygous in many isolates [37,39,58,59]. ii) Previous studies observed Pst isolates with a low virulence spectrum tended to be highly heterozygous [39,60].…”
Section: Discussionmentioning
confidence: 92%
“…However, omission of haplotigs in the genome analysis may miss some important information. Due to the lack of phased assembles as reference genomes, previous association studies to identify effector candidates on Pst and Pt focused only on primary contigs [39,40]. In the present study, we detected SNPs and Indels from both primary scaffolds and haplotigs and conducted association analysis using all identified variants.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One additional Psh isolate (04–051) was sequenced using the Ion Proton technology following the previously described method [ 64 ]. This isolate was collected from Oregon, Washington in 2004 and was virulent on barley differentials Topper, Heils Franken, Hiproly, Abed Binder 12, Trumpf, I 5 and Bancroft but avirulent on the remaining barley differentials (Emir, Astrix, Varunda, Mazurka and Bigo) and all wheat differentials for identifying Pst races.…”
Section: Methodsmentioning
confidence: 99%